793 The Giant Hogweed as A Rare Cause of Chemical Burns: A Case Series. (4th May 2021) - Lim, S K; Clements, J; Khan, K
Abstract: Introduction: The Giant Hogweed (Heracleum mantegazzianum) is a rare cause for chemical burns in humans and animals and is acquiring growing recognition in mainstream media as a relevant public health concern. Injuries attributed to this plant range from innocuous superficial irritation to full-thickness chemical burns. A vast majority of cases will resolve with conservative measures and effective first aid, but these case series demonstrate the clinical course of more severe injuries. Description: We present a case series of 2 patients requiring admission to the Royal Group Hospitals for management of mixed thickness hogweed burns. Injuries were sustained by two separate infestations of giant hogweed in the Western Trust Area. Both patients responded to observation and conservative measures, namely effective analgesia, UV light protection, topical hydrocortisone, and dressings. Discussion: Cutaneous burns induced by giant hogweed are caused by contact with its photoactive sap containing plant furocoumarins. On exposure to sunlight, the sap initiates a damaging process known as phytophotodermatitis (PPD). This process can be managed effectively with topical steroids; however, prolonged contact and subsequent sun exposure may lead to more severe skin damage. In extremely rare instances, damage may progress to full-thickness skin burns warranting operative intervention.